Effectiveness of Mindfulness Training on Sleep Problems and Depression in Adolescents - Chitsaz, Mahdi; Ahmadi, Ezzatollah; Bafandeh Qaramaleki, Hassan (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: The present study aimed to determine the effectiveness of mindfulness-based intervention on sleep problems and depression in adolescents.Methods and Materials: This research was a quasi-experimental study with a pre-test and post-test design, along with a control group. The statistical population included all high school students with sleep problems in the city of Azarshahr during the 2023-2024 academic year. A sample of 30 individuals was selected using the Depression Anxiety Stress Scales (DASS) by Lovibond and Lovibond (1995) and the Insomnia Severity Index (ISI) by Morin (1993) through purposive sampling methods. They were randomly assigned to experimental and control groups. Data analysis was conducted using covariance analysis in SPSS version 25.Results: Data analysis revealed that the mindfulness-based intervention resulted in a significant difference between the groups in terms of depression (0.71) and insomnia problems (0.55) (p < .05).Conclusion: According to the findings, it can be suggested that mindfulness-based intervention reduces depression and sleep problems.